HGG-01. ENTRECTINIB IN RECURRENT OR REFRACTORY SOLID TUMORS INCLUDING PRIMARY CNS TUMORS: UPDATED DATA IN CHILDREN AND ADOLESCENTS. (4th December 2020) - Robinson, Giles; Desai, Ami; Basu, Ellen; Foster, Jennifer; Gauvain, Karen; Sabnis, Amit; Shusterman, Suzanne; Macy, Margaret; Mease, Luke; Yoon, Janet; Cash, Thomas; Abdelbaki, Mohamed; et al.
Abstract: STARTRK-NG (phase 1/2) is evaluating entrectinib, a CNS-penetrant oral, TRK/ROS1/ALK tyrosine kinase inhibitor, in patients <21 years with recurrent/refractory solid tumors, including primary CNS tumors. After determining the recommended dose, 550mg/m 2 /day, in all-comers, expansion cohorts with gene-fusion-positive CNS/solid tumors ( NTRK1/2/3, ROS1 ) are being enrolled. As of 5Nov2019 (data cut-off), 39 patients (4.9m–20y; median 7y) have been evaluated for response, classified as complete (CR) or partial response (PR), stable (SD) or progressive disease (PD) using RANO (CNS), RECIST (solid tumors), or Curie score (neuroblastoma). Responses in patients with fusion-positive tumors were Investigator-assessed (BICR assessments are ongoing) and occurred at doses ≥400mg/m 2 . Best responses in fusion-positive CNS tumors (n=14) were: 4 CR ( GKAP1-NTRK2, ETV6-NTRK3 [n=2], EML1-NTRK2 ); 5 PR ( KANK1-NTRK2, GOPC-ROS1, ETV6-NTRK3, TPR-NTRK1, EEF1G-ROS1 ); 3 SD ( BCR-NTRK2, ARHGEF2-NTRK1, KIF21B-NTRK1 ); 2 PD ( PARP6-NTRK3, EML4-ALK ); and in fusion-positive solid tumors (n=8) were: 3 CR ( ETV6-NTRK3 [n=2], DCTN1-ALK ); 5 PR ( EML4-NTRK3, TFG-ROS1 [n=3], KIF5B-ALK ). Responses (Investigator-assessed) in non-fusion tumors (n=17) were: 1 CR ( ALK F1174L mutation), 3 SD, 10 PD, 3 no data/unevaluable. The objective response rate (CR+PR/total) in patients with fusion-positive tumors was 77% (17/22) versus 6% (1/17) in those with non-fusion tumors. All 39 patients experienced ≥1 adverse event (AE); the most frequent AEs included weight gain and anemia (both 48.7%); increased ALT, increased AST, cough and pyrexia (all 46.2%); increased creatinine and vomiting (both 43.6%); and bone fractures (n=10, in 9 patients). Entrectinib has produced striking, rapid, and durable responses in solid tumors with target gene fusions, especially high-grade CNS neoplasms.